Kinetic processes in negative glow plasma of low pressure discharge in oxygen - Tsiolko, V.V.; Matsevich, S.V.; Bazhenov, V.Yu.; Piun, V.M; Ryabtsev, A.V. (Вопросы атомной науки и техники, 2013)
It is shown that electron energy distribution function of negative glow plasma of low pressure discharge in oxygen exhibits two-temperature behavior due to the influence of metastable molecules O²(a¹Δg), O²(b¹Σ+g) and excitation of O² vibrational levels. As well, spatial dependencies of the atomic oxygen concentration on the gas pressure and power density in the discharge plasma are determined by actinometry method. Показано, що функція розподілу електронів по енергіях плазми негативного світіння розряду низького тиску в кисні має двотемпературний характер із-за впливу метастабільних молекул O²(a¹Δg), O²(b¹Σ+g) та збудження коливальних рівнів О². Методом актинометрії встановлено просторові залежності концентрації атомарного кисню від тиску газу та питомої потужності в розряді. Показано, что функция распределения электронов по энергиям плазмы отрицательного свечения разряда низкого давления в кислороде имеет двутемпературный характер из-за влияния метастабильных молекул O²(a¹Δg), O²(b¹Σ+g) и возбуждения колебательных уровней О². Методом актинометрии установлены пространственные зависимости концентрации атомарного кислорода от давления газа и удельной мощности в разряде.